The relation between corporate social responsibility and profit shifting of multinational enterprises - Michael Overesch; Sina Willkomm (International Tax and Public Finance, 2024)
We examine the relation between corporate social responsibility [CSR] and international profit shifting. We find consistent evidence that CSR is adversely related to profit shifting within European and US multinational firms. Additional results document that less profit shifting occurs in multinational firms that show high performance in the social or corporate governance dimensions. For US multinational firms, we find that the CSR performance is negatively related to profit shifting, particularly if a multinational firm faces fewer reputational concerns or competitive threats. Our findings point to a corporate culture in which, for international tax planning through profit shifting, CSR and tax payments complement each other.
Keywords: H25; H26; M14; 340; Profit shifting; Corporate social responsibility; Tax avoidance; Corporate governance